Trin Bonner: capstone - Bonner, Trin, artist (Colorado State University. Libraries, 2025)
The artist's statement: My name is Trin, and I am a Graphic Designer and Illustrator. Cartoon characters and vibrant, fun world-building inspire me. Growing up on Cartoon Network and Nickelodeon heavily influenced the kind of art I love to consume and create. My work explores character design and imaginative worlds within the context of graphic design. I'm especially interested in the interaction between typographic systems and illustration—my process is guided by a sense of fun and nostalgia. When I design brand identities, I embrace illustrative elements, expressive type, and bold colors. I believe the graphic design world could benefit from a bit more playfulness. While delivering a clear message is essential, I aim to do so in a way that also brings joy or a smile to the viewer's face. I primarily use Adobe Creative Suite for design and Krita for illustration.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design